Use of morphometric parameters for tracking ovule and microspore evolution in grapevine (Vitis vinifera L., cv. ‘Aragonez’) and evaluation of their potential to improve in vitro somatic embryogenesis efficiency from gametophyte tissues - Cardoso, Hélia (2012)
Somatic embryogenesis induction from in vitro cultured stamens and carpels is highly dependent on explants’ inoculation at specific developmental stages. To establish good correlations between measurable morphometric parameters of flowers or flower buds and developmental stages of micro- and macrosporogenesis, this procedure is the easiest way to simplify the in vitro culture procedures. These correlations were established here for the most important Iberian grapevine cultivar, the “Aragonez”, named “Tempranillo” in Spain and “Tinta Roriz” in the north of Portugal, and were based in floral buds and anther measurements. The anther length, with a correlation coefficient of 0.90, proved to be the best morphometric parameter to follow microsporogenesis evolution. A correlation between micro- and macrosporogenesis evolutionary stages was also positively established, allowing the use of morphometric parameters for tracking ovule evolution as well. Carpels in several evolutionary stages were in vitro cultured to evaluate the aging effect on the capacity for somatic embryogenesis induction. Explants inoculated in the earliest stages of macrosporogenesis presented the best results. Media culture formulations were also tested for ovary culture, with the best results being achieved with a 5:1 auxin/cytokinin ratio.